Understanding the benefits and challenges of Content and Language Integrated Learning (CLIL) in English education: a literature synthesis - Mohammad Iskandar Dzulkurnain; Sugeng Irianto; Rasmita Rasmita; Lulu Jola Uktolseja; Wira Jaya Hartono; Tagor Manurung (Journal on Education, 2024)
Content and Language Integrated Learning (CLIL) is a dynamic educational approach that holds the potential to enhance language proficiency, content knowledge acquisition, and academic achievement among students. By integrating language learning with subject content, CLIL provides students with immersive and meaningful learning experiences that facilitate communicative competence, critical thinking skills, and intercultural awareness. Discussions surrounding CLIL implementation have emphasized its potential to transform language education and promote multilingualism in diverse educational contexts. Key findings from research on CLIL suggest that participation in CLIL programs can lead to improvements in students' language proficiency across various linguistic skills, including listening, speaking, reading, and writing. Additionally, CLIL facilitates deeper comprehension and retention of subject matter by providing authentic contexts for learning and promoting interdisciplinary connections. Students participating in CLIL programs demonstrate comparable or even superior levels of content knowledge acquisition compared to those in traditional subject-based instruction, highlighting the effectiveness of CLIL in promoting academic success and critical thinking skills. However, the success of CLIL implementation hinges on various factors, including teacher preparation, institutional support, and resource allocation. Educators play a central role in the success of CLIL programs, requiring specialized training and ongoing professional development to effectively integrate language and content instruction. Institutional support is essential for creating conducive environments for CLIL implementation, while adequate resources are critical for optimizing learning experiences and addressing the diverse needs of learners.